2017
DOI: 10.1063/1.4997233
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of the electronic structure of indium and gallium chalcogenide bilayers

Abstract: Using first principle calculations, we have studied the structural and electronic properties of two dimensional bilayers of indium and gallium chalcogenides. With density functional theory corrected for van der Waals interactions, the different modes of stacking were investigated in a systematic way, and several of them were found to compete in energy. Then, their band structures were obtained with the GW approximation and found to correspond to indirect bandgap semiconductors with a small dependency on the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…From this value of η 0 and Eq. 12, we estimate that E B = 15 meV/Å 2 for InSe, within the range of values of E B reported for other vdW crystals [80].…”
Section: A Elastic Properties Of Inse and Hbnsupporting
confidence: 85%
“…From this value of η 0 and Eq. 12, we estimate that E B = 15 meV/Å 2 for InSe, within the range of values of E B reported for other vdW crystals [80].…”
Section: A Elastic Properties Of Inse and Hbnsupporting
confidence: 85%
“…Single-layer group-III monochalcogenides in hexagonal structure 16,[30][31][32][33] gathered attention also for their in-triguing thermoelectric properties. Interestingly, theoretical and experimental results demonstrate that they present so-called Mexican-hat shape dispersion at their valence band maximum (VBM), and consequently gives rise to Van-Hove singularity 34 in the density of states (DOS) near VBM [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line). The band structure analysis of mono-and few-layer InSe [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has revealed that the conduction and valence band edges near the Γ-point are non-degenerate, being dominated by s and p z orbitals of both metal and chalcogen atoms. Combined with the opposite z → −z (mirror reflection) symmetry of conduction and valence bands, this determines that the transition across the principal band gap has a dominantly electric dipole-like character, coupled to out-of-plane polarized photons.…”
Section: Introductionmentioning
confidence: 99%